2023
DOI: 10.1037/pas0001192
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the predictive accuracy of structured and unstructured risk assessment methods for the prediction of recidivism in individuals convicted of sexual and violent offense.

Abstract: One of the most commonly replicated results in the research area of recidivism risk assessment is the superiority of structured and standardized prediction methods in comparison to unstructured, subjective, intuitive, or impressionistic clinical judgments. However, the quality of evidence supporting this conclusion is partly still controversially discussed because studies including direct comparisons of the predictive accuracy of unstructured and structured risk assessment methods have been relatively rarely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…In modern psychiatry, the purpose of risk assessment is to identify and prevent potential harmful events, such as suicidality or violence. Risk assessment strategies can be divided into unstructured professional judgement (UPJ), and structured methods, that is, actuarial risk assessment instruments (ARAI’s) and structured professional judgements (SPJ) ( 1 ). While UPJ reflects a personal intuition or opinion, structured methods use observable static and dynamic risk factors ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In modern psychiatry, the purpose of risk assessment is to identify and prevent potential harmful events, such as suicidality or violence. Risk assessment strategies can be divided into unstructured professional judgement (UPJ), and structured methods, that is, actuarial risk assessment instruments (ARAI’s) and structured professional judgements (SPJ) ( 1 ). While UPJ reflects a personal intuition or opinion, structured methods use observable static and dynamic risk factors ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the predictive validity using a checklist format with actuarial statistical methods produced better results than clinicians' predictions without checklist format (Desmarais et al, 2018;Howell et al, 2014). Recent analyses have also reconfirmed the superiority of insurance statistics over unstructured clinical judgment in predicting recidivism (Wertz et al, 2023).…”
mentioning
confidence: 96%
“…5 In relation to treatment of ICSO it is essential to address the psychosocial sequelae posed by comorbid mental disorders as well as specific criminogenic needs, particularly in treatment aiming to reduce reoffending. 3,6,7,11 Evidence of the effect of various treatment approaches of criminogenic needs in other patient groups (offenders/psychiatric samples) could guide the development of specific treatment approaches for ICSO. The subgroup-analysis in the Biedermann study 8 also points to the importance of conducting such an analysis given the fact that the ICSO group is heterogenic, necessitating different treatment approaches for the respective subgroups, especially specialized treatment of paraphilic disorders in ICSOC.…”
mentioning
confidence: 99%
“…The finding that adding information about mental disorders did not increase the predictive value of the wellestablished structured risk assessment tools points to the importance of implementing validated risk assessment tools/checklists in the assessment and management of ICSO reoffending risk. Unstructured clinical judgment (UCJ) still appears to be the frequently applied risk assessment method in clinical practice, 11,12 despite several studies showing low predictive accuracy of UCJ across cultural and clinical contexts. 11,13 Yet, there is still a need for ecological field studies evaluating the accuracy of risk assessments conducted by experienced clinicians in real-world settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation